2016
DOI: 10.1155/2016/6012896
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reduction of CO2Using TiO2-Graphene Nanocomposites

Abstract: TiO2-graphene (TiO2-RGO) nanocomposites were preparedviaa simple chemical method by using graphene oxide (GO) and TiO2nanoparticles as starting materials. The morphologies and structural properties of the as-prepared composites were characterized by X-ray diffraction, Raman spectroscopy, N2adsorption-desorption measurements, and transmission electron microscopy. TiO2-RGO nanocomposites exhibited great photocatalytic activity toward reduction of CO2into CH4(2.10 μmol g−1 h−1) and CH3OH (2.20 μmol g−1 h−1), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…After 6 h of reaction, the yield of CH 4 was 1.718 µmol•gcatalyst −1 •h −1 , which has significantly improved light stability, and maintains 95.8% reactivity, even after six hours of light exposure. Liu et al [24] prepared TiO 2 -RGO as a photocatalyst, and the yields of CH 4 MOF is a three-dimensional crystalline microporous material composed of metal oxygen clusters and organic connecting molecules. It has a large surface area and porosity, and has high flexibility in adjusting structure and composition.…”
Section: Photocatalyticmentioning
confidence: 99%
“…After 6 h of reaction, the yield of CH 4 was 1.718 µmol•gcatalyst −1 •h −1 , which has significantly improved light stability, and maintains 95.8% reactivity, even after six hours of light exposure. Liu et al [24] prepared TiO 2 -RGO as a photocatalyst, and the yields of CH 4 MOF is a three-dimensional crystalline microporous material composed of metal oxygen clusters and organic connecting molecules. It has a large surface area and porosity, and has high flexibility in adjusting structure and composition.…”
Section: Photocatalyticmentioning
confidence: 99%
“…Several studies [1,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] were reported on CO 2 reduction to methanol using photocatalysts in aqueous medium. Among various semiconducting photocatalyst materials, TiO 2 was found the most feasible by various authors to use for the reduction of carbon dioxide in aqueous medium [1,35,38,39,41,42,44,47,[49][50][51][52]. This is for the reason that high band gap semiconductors were needed to overcome the high thermodynamic barrier involving CO 2 reduction coupled with water oxidation in an aqueous medium.…”
Section: Photocatalytic Reduction Of Co 2 To Methanolmentioning
confidence: 99%
“…The best photocatalyst was prepared after annealing at 300 • C with yields of CH 4 and CO of 4.1 and 2.5 µmol/g/h for solar light, and 0.53 and 0.63 µmol/g/h for visible light, respectively. J. Liu et al [15] proposed a TiO 2 -graphene nanocomposite prepared using GO and TiO 2 nanoparticles mixed in a suspension with water, sonicated, and then heated in an oil bath. The photoactivity upon reduction of CO 2 to CH 4 (2.1 µmol/g/h) and CH 3 OH (2.2 µmol/g/h) was attributed to the synergistic effect between TiO 2 and graphene.…”
Section: Introductionmentioning
confidence: 99%